Inoculation with extreme endophytes improves performance and nutritional quality in crop species grown under exoplanetary conditions - Molina-Montenegro, Marco A.; Escobedo, Victor M.; Atala, Cristian (Frontiers in Plant Science, 2023)
Introduction: Technological advances have made possible long space travels and even exoplanetary colonies in the future. Nevertheless, the success of these activities depends on our ability to produce edible plants in stressful conditions such as high radiation, extreme temperatures and low oxygen levels. Since beneficial microorganisms, such as fungal endophytes from extreme environments, have helped agriculture cope with those difficulties, endophytic fungi may be a putative tool to ensure plant growth under exoplanetary conditions. Additionally, growing crops in polyculture has been shown to increase productivity and spatial efficiency, which is essential given the likely space restrictions in such conditions. Methods: We evaluated the effect of the inoculation with a mix of two fungal endophytes from the Atacama Desert on performance (survival and biomass) and nutritional quality of three crop species (lettuce, chard and spinach) grown under exoplanetary conditions. In addition, we measured the amount of antioxidants (flavonoids and phenolics) as possible mechanisms to cope with such abiotic conditions. The exoplanetary conditions were; high UV radiation, low temperature, low water availability, and low oxygen levels. These crops were put in growing chambers in monoculture, dual culture and polyculture (the three species in the same pot) for 30 days. Results and Discussion: Our results show that inoculation with extreme endophytes improved survival by ca. 15 - 35% and biomass by ca. 30 - 35% in all crop species. The most evident increase was when grown in polyculture, except for survival in spinach, where inoculated plants had higher survival only in dual culture. Nutritional quality and the amount of the antioxidant compounds antioxidants increased in all crop species when inoculated with the endophytes. Overall, fungal endophytes isolated from extreme environments such as the Atacama Desert, the driest desert in the world, could be a key biotechnological tool for future space agriculture, helping plants cope with environmental stress. Additionally, inoculated plants should be grown in polyculture to increase crop turnover and space-use efficiency. Lastly, these results provide useful insights to face the future challenges of space-farming.